Desempenho de caprinos Saanen, na recria, alimentados com dieta contendo bandinha de feijão - Juliana Costa Cordeiro (2008)
The aim of this work was to determine voluntary intake and apparent digestibility of dry matter (DM), crude protein (CP) and fibrous fractions (NDF and ADF) of diets containing broken bean; to evaluate carcass cuts and viscera Saanen kid goats breed fed with different levels of broken bean in concentrate through the ultrasonic technique as well as correlating the yields characteristics with biometrics measures. Fourteen Saanen kid goats breed were used, with 90 days of age and weighing 12,83 kg; divided in two treatments, the first with 30% of broken bean included in the concentrate, and the second with 60% of inclusion. The rations were isoproteinous and isoenergetic and they were calculated in according to NRC (1985). Voluntary intake and apparent digestibility of DM, CP, NDF, ADF and hemicelulose were studied. Also, evaluated the nitrogen balance, voluntary intake behavior and glicemic curve of these animals. The animals were weighed and measured periodically, through measured biometrics and ultrasonic. Second, were abated and carcass; organs, viscera weighed. Carcass pH and temperature were appraised for 24 hours. The carcass yields, cuts and viscera were calculated. Broken bean didn't alter the voluntary intake and apparent digestibility of dry matter, neutral detergent fiber, acid detergent fiber and hemicelulose. Crude protein intake made possible nitrogen balance positive. No modification in intake kid goats Saanen behavior was observed. The proportions of glucose plasmatic concentration were different along the day. During the studied phase, kids goats presented isometric development, independent of sex and diet consumed. The biometric and ultrasonic measurement can be used to predict kid goats Saanen carcass characteristics fed with broken bean, and ultrasonic evaluations in the breastbone should be preferred due to largest variation source in readings. The inclusion of beak bean in kids goats diet didn't affect the physical-chemical parameters of meat, as well as, covering fat deposition. The animals sex in that phase didn't impose changes in carcasses characteristics. Kids goats carcasses pH didn't reduce at desirable levels, and had faster cooling because of covering fat absent.